Ownership and performance of microfinance institutions: Empirical evidences from India - Asif Khan; Alam Ahmad; Saba Shireen (Cogent Economics & Finance, 2021)
The study examines the efficiency differences across the ownership structure of Indian microfinance institutions (MFIs) operating during the year 2005/06 to 2017/18 in response to regulatory reforms initiated by the Reserve Bank of India (RBI) in the year 2011. We remove the outliers from the dataset first. Thereafter, we employ the bootstrap data envelopment analysis (DEA) to assess the bias-corrected efficiency scores. To identify the performance determinants, we use bootstrap truncated regression. The empirical results suggest that the performance difference between NBFCs and Non-NBFC MFIs is not statistically significant in the sample period. Further, the study finds that the size and ownership structure of MFI has a positive and statistically significant impact on the efficiency level. Although the coefficient of PAR30 (Portfolio at risk, 30 days) is statistically insignificant, however, the results conclude that the deteriorating credit quality has hindered the efficiency level. The Indian MFI industry needs to focus on the adoption of more innovative technology and partnership with FinTech (financial technology) firms to reduce the transaction costs and service time. The RBI essentially endorses the regulatory-sandbox practices to offer micro-financial services to the poor.
Keywords: G21; G23; 330; bootstrap DEA; bootstrap truncated regression; efficiency; Indian MFIs; Microfinance institutions; ownership structure; regulatory framework